2019
DOI: 10.1016/j.ijcha.2019.100358
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage closure with WATCHMAN in Asian patients: 2 year outcomes from the WASP registry

Abstract: Background Left atrial appendage closure is a non-pharmacological alternative for stroke prevention in high-risk non-valvular atrial fibrillation patients, but has not been widely studied in Asian patients. The prospective WASP registry assessed real-world outcomes for patients undergoing WATCHMAN implant in the Asia-Pacific region. Methods Data were collected from consecutive patients across 9 centres. Major endpoints included procedural success, safety and long-term o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 22 publications
0
40
0
Order By: Relevance
“…Comparison of results from the series of patients who underwent LAAC may show variations in the percentage of events during follow-up. In spite of some consistency in the relative reduction of stroke (60-80% of CHA2DS2-VASc (congestive heart failure, hypertension, age, diabetes, stroke history, vascular disease, sex) scores), there was a higher variability in bleeding events among the series from the first year of follow-up, with major bleeding events ranging from 2.2% to 10% per year [2][3][4].…”
Section: Introductionmentioning
confidence: 91%
“…Comparison of results from the series of patients who underwent LAAC may show variations in the percentage of events during follow-up. In spite of some consistency in the relative reduction of stroke (60-80% of CHA2DS2-VASc (congestive heart failure, hypertension, age, diabetes, stroke history, vascular disease, sex) scores), there was a higher variability in bleeding events among the series from the first year of follow-up, with major bleeding events ranging from 2.2% to 10% per year [2][3][4].…”
Section: Introductionmentioning
confidence: 91%
“…quently in SALUTE. 8 Recently, the WASP registry reported that the mean LAA diameter was significantly larger in Asians and the median device size used was 27 mm for Asians vs. 24 mm for non-Asians, 10 suggesting that the LAA in Asians might be larger than in other races.…”
Section: Subject Demographics and Follow-up Compliancementioning
confidence: 99%
“…Only one patient experienced WATCHMAN device deployment failure due to an oversized LAA. A WASP study showed that the average LAA ostium diameter was significantly larger in Asian populations, thus requiring larger WATCHMAN devices ( 23 ). Therefore, based on our experience, we recommend the thorough pre-procedural evaluation of LAA morphology as well as larger LAAC devices to accommodate LAA in Asian populations.…”
Section: Discussionmentioning
confidence: 99%